Camouflage. (Edinburgh : Scottish Arts Council, 1988)
Brodsky, Horace ; Wadsworth, Edward ; Haacke, Hans ; Trockel, Rosemarie ; Cragg, Tony ; Goldworthy, ANdy ; Holzer, Jenny ; Lavier, Bertrand ; Nash, David ; etc.
published on the occasion of the touring exhibition, Camouflage, 1988
boek